Effects of auricular acupuncture stimulation on healthy adults’ upper limb motor-evoked potentials: A randomized, crossover, double-blind study - Zhang, Jin; Huang, Wen-Hao; Zheng, Ya-Dan; Li, Xin; Jiang, Hao-Xiang; Su, Min-Zhi; Huang, Xiao-Yan; Dou, Zu-Lin; Tang, Zhi-Ming (Frontiers in Neuroscience, 2022)
Objective: The aim of this study was to determine whether auricular acupuncture has neuromodulatory effects on the motor cortex of healthy adults. Methods: Fourteen healthy subjects received a real auricular acupuncture stimulation (SF1) session and a sham acupuncture stimulation session. The interval between the two types of stimulation was more than 24 hours. A finger finger dexterity test (taping score and taping speed by using ipad) was assessed , and motor-evoked potentials (MEP) were assessed before and after each stimulation. Results: Before the treatment, there were no significant differences in MEP amplitude, tapping score, or tapping speed (P > 0.05) between the real and sham stimulation conditions. After the treatment, the MEP amplitude, tapping score, and tapping speed in the real stimulation condition increased significantly compared to the pre-stimulation measurements and were significantly higher than those in the sham stimulation condition (P < 0.01). In the sham stimulation condition, the MEP amplitude, tapping score, and tapping speed decreased significantly compared to the pre-stimulation measurements (P < 0.05). Conclusion: Acupuncture of auricular points can modulate the excitability of the motor cortex area of controlling the upper limbs. Keywords: cerebral motor cortex, auricular acupuncture, transcranial magnetic stimulation, brain excitability, upper limb function